A mixed‐method study of pain management practice in a UK children's hospital: identification of barriers and developing strategies to maintain effective in‐patient paediatric pain management. Issue 1 (1st October 2015) - Beckett, Kate; Henderson, Ellen M.; Parry, Sarah; Stoddart, Peter; Fletcher, Margaret
Abstract: Aim: To assess Acute Pain Service and paediatric pain management efficacy in a UK specialist paediatric hospital to inform wider recommendations for future sustainability. Background: UK paediatric acute pain services vary. Although comprehensive pain management guidelines exist, consensus on the best model of care is lacking. Worldwide, medical and pharmacological advances and rapid patient turnover have increased the challenges of managing hospitalized children's pain. Simultaneously nurses, who deliver the bulk of pain management, have experienced reduction in skill mix and training opportunities. Specialist Acute Pain Services have evolved to meet these demands; their overall efficacy is unknown. Design: This mixed‐methods study explores pain management practice at a UK paediatric hospital to assess current efficacy and future sustainability. Method: A 2013 case note review of all Acute Pain Services referrals over 14 days were compared with an interval sample of concurrent non‐referred inpatient children; seven semi‐structured interviews were conducted with a range of clinical staff. Results: Twenty‐two referrals of 15 children were made; 15 comparison children were identified. All 30 children (100%) were appropriately referred/non‐referred. Acute Pain Services cases experienced higher pain levels, were more likely to have long term conditions, longer hospital stay and repeat admissions. Three key themes emerged through interview analysis: 'addressing pain', 'changing contexts' 'pain as an "expert" skill'. Increased specialization, reduced clarity between different pain modalities and decreased training opportunities had resulted in potentially unsustainable APS dependence.